Engineered Fabrication of Enamel-Mimetic Materials. (July 2022) - Zhang, Lingyun; Zhang, Yunfan; Yu, Tingting; Peng, Liying; Sun, Qiannan; Han, Bing
Abstract: Tooth enamel, which is a biological tissue mainly composed of well-aligned hydroxyapatite nanocrystals and an interlaced protein matrix, has remarkable mechanical and aesthetic behaviors. Nevertheless, it is challenging to regenerate enamel naturally, and potential pulp involvement and tooth loss may occur. As the hardest biogenic composite material, enamel has long been regarded as a promising load-bearing material. Thus, understanding the enamel formation process and enamel structural motif mechanisms is important for the design and engineering of high-performance biomimetic composites with high strength and physical resilience. Extensive studies have been conducted on mimicking the microstructure and mechanical properties of tooth enamel, and various enamel-like material synthesis protocols have been developed. In light of the engineering fabrication of enamel-like materials, this review focuses on recent progress in synthetic strategies for enamel-mimetic materials and provides a discussion of the potential applications of these materials.